2022
DOI: 10.3389/fmars.2022.910467
|View full text |Cite
|
Sign up to set email alerts
|

Multi-habitat seascape restoration: optimising marine restoration for coastal repair and social benefit

Abstract: Marine ecosystem restoration is fast becoming the primary tool for repairing the socio-ecological functions and economic benefits of coastal ecosystems. Healthy seascapes are characterized by many interacting species and intermingled habitats (e.g., seagrass, kelp, shellfish, sedimentary) that co-create ecological functions of substantial socio-economic value. These co-created functions not only build stability and resilience at seascape scales, but synergistically combine to enhance ecological productivity th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…The influence of different habitats on oyster reef communities also provides opportunities for co-restoration with other foundation species (seagrass and mangroves; e.g. McAfee et al 2022) and landscape-scale management approaches to further tailor the communities that establish.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of different habitats on oyster reef communities also provides opportunities for co-restoration with other foundation species (seagrass and mangroves; e.g. McAfee et al 2022) and landscape-scale management approaches to further tailor the communities that establish.…”
Section: Discussionmentioning
confidence: 99%
“…It has been showed that where multiple interconnected habitats are co‐restored, their positive interactions mutually benefit each other to stabilize and even accelerate ecosystem recovery (McAfee et al, 2022a). This has been well documented in case studies from South Australia, which showed how constructed boulder reefs provide opportunities to co‐restore shellfish and kelp forests, while stabilizing sediment for seagrass recovery.…”
Section: Envisioning a Restoration‐focused Eb‐msp Framework Through E...mentioning
confidence: 99%
“…Moreover, considering the interconnected multi‐habitat approach also gives more chance to increase the connectivity between carbon source and sink habitats (e.g. between adjacent kelp forests and seagrass, respectively) and, through enhanced organic carbon transfer and burial, maximize the carbon sequestration potential (Smale et al, 2018; McAfee et al, 2022a).…”
Section: Envisioning a Restoration‐focused Eb‐msp Framework Through E...mentioning
confidence: 99%
See 1 more Smart Citation
“…Within this framework, the implementation of active and coordinated efforts for vermetid reef conservation should be an intergovernmental priority. Planning how to face local vermetid decline by successful restoration strategy should also consider biological interactions and the adoption of a multispecies approach (McAfee et al, 2022).…”
Section: Introductionmentioning
confidence: 99%